1995
DOI: 10.1007/bf00125312
|View full text |Cite
|
Sign up to set email alerts
|

The chicken muscle thick filament: temperature and the relaxed cross-bridge arrangement

Abstract: Although chicken myosin S1 has recently been crystallized and its structure analysed, the relaxed periodic arrangement of myosin heads on the chicken thick filament has not been determined. We report here that the cross-bridge array of chicken filaments is temperature sensitive, and the myosin heads become disordered at temperatures near 4 degrees C. At 25 degrees C, however, thick filaments from chicken pectoralis muscle can be isolated with a well ordered, near-helical, arrangement of cross-bridges as seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 74 publications
(113 reference statements)
7
24
1
Order By: Relevance
“…This effect of temperature on helical order appears small compared to that in rabbit 22,25 or chicken thick filaments. 21 We also found no such temperature effect with any other nucleotide. These results suggest a small temperature dependence for the open to closed transition in tarantula myosin, which might also occur in myosin from other cold-blooded animals whose thick filaments are well ordered in the relaxed state at low temperature (like frog and fish [23][24][25].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This effect of temperature on helical order appears small compared to that in rabbit 22,25 or chicken thick filaments. 21 We also found no such temperature effect with any other nucleotide. These results suggest a small temperature dependence for the open to closed transition in tarantula myosin, which might also occur in myosin from other cold-blooded animals whose thick filaments are well ordered in the relaxed state at low temperature (like frog and fish [23][24][25].…”
Section: Discussionmentioning
confidence: 78%
“…18 This suggestion was supported by X-ray diffraction patterns of rabbit skeletal muscle exposed to different nucleotides at different temperatures 19 (although the possibility of a coupling between the helical order and a specific conformation of the myosin head that may depend on the bound nucleotide was also considered as an alternative). However, while warm-blooded animals (chicken as well as rabbit) require warm temperatures (O20 8C) for helical ordering, [18][19][20][21][22] cold-blooded animals, such as frog and fish, do not, [23][24][25] and the dependence of helical order on the chemical state of ATP in thick filaments from cold-blooded animals has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The number of helices in the thick filaments was found to be either 3 in vertebrates (frog, Kensler and Stewart 1983;rabbit, Kensler and Stewart 1993), 4 in arthropods (Limulus, (Stewart et al 1981;tarantula, Crowther et al 1985;Padrón et al 1993a;and scorpion, Stewart et al 1985) or 7 in mollusks (scallop, Vibert and Craig 1983;Craig et al 1991). Other EM studies on negatively stained thick filaments have been reported for invertebrates such as the indirect flight muscle (IFM) of the giant water bug Lethocerus indicus (Insecta) (Clarke et al 1986;Morris et al 1991), as well as for skeletal muscle in several vertebrates such as goldfish Carassius auratus (Kensler and Stewart 1989;Eakins et al 2002), frog Rana pipiens Stewart and Kensler 1986), chicken (Kensler and Woodhead 1995) and rabbit (Kensler and Stewart 1993). However, none of these studies achieved enough resolution to resolve both heads in the thick filaments 3D reconstruction.…”
Section: Why Tarantula Muscle?mentioning
confidence: 99%
“…The tannic acid was at a concentration of 0.25% (MallincKrodt AR 1764, MallincKrodt, St. Louis, MO). All of the rinse and stain solutions were maintained at 25°C on a Thermolyne Dri-bath heater to avoid the loss of helical ordering which has been demonstrated to occur for mammalian and avian thick Wlaments at temperatures below »15°C (Kensler and Woodhead, 1995;Kensler et al, 1994).…”
Section: Negative Stainingmentioning
confidence: 99%
“…We previously used a similar approach to successfully delineate the structure of isolated skeletal muscle thick Wlaments from frog, Wsh, chicken, and rabbit skeletal muscles (Kensler and Stewart, 1983, 1986, 1993Kensler and Woodhead, 1995;Kensler et al, 1994;Stewart and Kensler, 1986).…”
Section: Introductionmentioning
confidence: 99%